DEVELOPMENT STRATEGY FOR THE DISADVANTAGED YOUTH IN RURAL AREA OF BANGLADESH - Hossain, Alamgir; Rahman, Mostafizur (European Scientific Journal, ESJ, 2012)
Poverty is common phenomena among rural area in Bangladesh due to the lack of education and knowledge of family planning, job opportunity. Normally in the rural area children will enroll school and about 40% of children give up their studies after completing one or two year education. So, they do not get any opportunity for job because of their incomplete education. CMES started an alternative education program for those helpless and disadvantage youth in the rural area of Bangladesh. They give them different practical training. Vatpara unit under Rajshahi district is one the unit where disadvantaged youth got training at different aspects. After analyzing the data of the 78 training participant’s of this unit we found that about 55% participants get job opportunity after completion the training from CMES. Most of the participants came from very poor family whose family’s yearly income is about TK 8000-13000 which is not enough to maintain family’s expenditure. So, most of participants did not get enough opportunity for general education. But after taking training from CMES they make themselves self employed and contribute his family to reduce poverty. So, CMES make significant role for the rural development by its effective program in Bangladesh.